1993
DOI: 10.1080/00288330.1993.9516573
|View full text |Cite
|
Sign up to set email alerts
|

Age validation and movement of freshwater eels (Anguilla dieffenbachiiandA. australis) in a New Zealand pastoral stream

Abstract: Forty-seven eels were captured, tagged, and released into a 420 m lowland section of the pastoral Ahirau Stream, North Island, New Zealand. Eels were marked with jet inoculations of alcian-blue dye, and plastic tube tags were surgically inserted into the gut cavity. Oxytetracycline hydrochloride was injected intraperitoneally to provide markers on otoliths. Over 3 years, 25 tagged eels were recaptured in the same stream reach, 16 of these within 20 m of their original sites of capture. All recaptured eels reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…The difference between these studies and ours presumably originated from the small width and high complexity of the Awirs stream, which offered numerous refuges and did not force the eels to move over long distances to find alternative refuges. Chisnall & Kalish (1993), who studied the movements of A. australis and A. dieffenbachii (Gray) by mark recapture also concluded to small scale (< 140 m) movements in a small stream of New Zealand. Similarly, Gunning & Shoop (1962) observed that A. rostrata occupied home ranges of less than 50 m in small Louisiana streams but were using larger ranges in wider streams.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between these studies and ours presumably originated from the small width and high complexity of the Awirs stream, which offered numerous refuges and did not force the eels to move over long distances to find alternative refuges. Chisnall & Kalish (1993), who studied the movements of A. australis and A. dieffenbachii (Gray) by mark recapture also concluded to small scale (< 140 m) movements in a small stream of New Zealand. Similarly, Gunning & Shoop (1962) observed that A. rostrata occupied home ranges of less than 50 m in small Louisiana streams but were using larger ranges in wider streams.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies on Anguilla rostrata have found that their yellow eel stage has a restricted home range and that individuals return to their initial habitat after foraging outside their territory (Bozeman et al 1985, Ford & Mercer 1986, Oliveira 1997, or return to their home range after being artificially displaced (Parker 1995). Similarly, studies of New Zealand eels concluded that the large eels have relatively small home ranges and typically only move short distances within these streams (Burnet 1969, Chisnall & Kalish 1993, Jellyman & Sykes 2003. However, within Lake Ellesmere, the constant removal of eels by the commercial fishery means that available habitat is always opening up.…”
Section: Habitat Use and Apparent Movementsmentioning
confidence: 99%
“…data). In a mark-recapture study in the pastoral Ahirau Stream (present study), the number of transparent zones following fluorescent labels (tetracycline) on the otoliths of tagged recaptured longfinned and shoitfinned eels corresponded to the number of years these eels were at liberty (Chisnall & Kalish 1993).…”
Section: Age Validationmentioning
confidence: 99%
“…Afterwards, eels are likely to live in specific areas, usually with limited home ranges (Burnet 1969;Jellyman & Todd 1982;Chisnall 1987;Chisnall & Kalish 1993). Growth Percentage of channel length as pool Water temperature is probably the most important factor causing habitat-specific growth differences in longfinned eels.…”
Section: Growth In Different Habitatsmentioning
confidence: 99%